Heavy metals in local and imported cosmetics in Ghana and their health risk assessment - Opoku Gyamfi; James Aboko; Edward Ankapong; Jemima Tiwaa Marfo; Nana Yaa Awuah-Boateng; Victor Agyei; Kofi Sarpong; Emmanuel Dartey (Taylor & Francis Group, 2023)
Abstract: This study aimed to determine the levels of heavy metal(loid)s in local and imported cosmetics purchased from the Kejetia market and to conduct their health risk assessment. Seven (7) metal(loid)s (Pb, Cd, As, Fe, Ni, Cr, and Hg) were analyzed in twenty-one (21) cosmetic samples. Atomic absorption spectroscopy (AAS) was used in this study. Some of the metal(loid)s in imported cosmetic samples were higher than those found in local cosmetic samples. However, there was no significant difference between the concentrations of the metal(loid)s in both local and imported cosmetic samples. The margin of safety (MoS) values for all the metal(loid)s in the cosmetics sample were below the WHO standard of 100. The HQ and HI values for almost all the metal(loid)s in the cosmetic samples were greater than their permissible limit of 1, suggesting that there may be health risks associated with using cosmetic samples for the sensitive sub-population. On the other hand, carcinogenic risk (CR) for Cr and As in local and imported cream and lotion were all higher than the tolerance levels. Moreover, from the results, the Pb, Cd, and Hg concentrations were higher than the acceptable permissible limits set by the various regulatory bodies. Cosmetic manufacturing industries are encouraged to adhere to the permissible limits set by regulators. We admonish the regulatory agencies to unforce regulations on permissible limits of heavy metals in cosmetics